Implementasi Pemanfaatan Aplikasi Canva dalam Meningkatkan Kreativitas Siswa Kelas VI SDN Kapuk 03 Pagi - H. Soro, Suharyanto; Sariningsih, Asih; Octavianti, Linda Nur; Mulyanah, Mulyanah (LP. Ma'arif Janggan Magetan, 2024)
In the increasingly rapid digital era, creativity is one of the skills that is very much needed. Students are required to be able to think creatively, innovatively, and be able to express their ideas in various ways. One way to facilitate the development of student creativity is to utilize existing technology, such as graphic design applications that can foster and improve critical thinking, communication, and collaboration skills. Conventional learning that tends to be monotonous is often less able to stimulate student creativity. Students need more interesting and interactive learning media to be able to develop their potential optimally. This study aims to determine the extent to which the Implementation of the use of the CANVA application in improving the creativity of grade VI students at SDN Kapuk 03 Pagi. This study uses a qualitative research paradigm with a case study approach. Data collection methods use observation, interview, and documentation methods. The results of the study show that (1) Utilization of the Canva application can improve student creativity in the learning process. (2). With the increase in student creativity, students are more enthusiastic and motivated in the learning process so that active, creative and interesting learning is created.